Concept and Design of a Hand-held Mobile Robot System for Craniotomy - Kane, Gavin J. (KIT Scientific Publishing, 2013)
This work demonstrates a highly intuitive robot for Surgical Craniotomy Procedures. Utilising a wheeled hand-held robot, to navigate the Craniotomy Drill over a patient's skull, the system does not remove the surgeons from the procedure, but supports them during this critical phase of the operation.